2014
DOI: 10.4161/pri.28388
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of anchorless prion protein, PrP226*, in the human brain

Abstract: It was shown previously that truncated molecules of prion protein can be found in brains of patients with some types of transmissible spongiform encephalopathy. One such molecule, PrP226*, is a fragment of prion protein, truncated at Tyr226. It was found to be present in aggregates, from which it can be released using chaotropic salts. In this study we investigated the distribution of PrP226* in Creutzfeldt–Jakob disease affected human brain, employing the mAb V5B2, specifically recognizing this fragment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…27 In addition to PrP-infected samples, we have shown that PrP226* is also present in the healthy brain, albeit in small amounts. 27,29 We are not the only research group to describe this PrP form. As indicated above, PrP226* was concurrently described by Jansen and coworkers.…”
Section: V5b2 and Prp226*mentioning
confidence: 67%
See 3 more Smart Citations
“…27 In addition to PrP-infected samples, we have shown that PrP226* is also present in the healthy brain, albeit in small amounts. 27,29 We are not the only research group to describe this PrP form. As indicated above, PrP226* was concurrently described by Jansen and coworkers.…”
Section: V5b2 and Prp226*mentioning
confidence: 67%
“…Analysis of aggregates in patients with sporadic Creutzfeldt-Jakob disease (sCJD) 27,28 and Gerstmann-Straussler-Scheinker (GSS) syndrome [29][30][31][32] has shown that apart from PrP Sc , aggregates are built from anchorless PrP and other variants of PrP without the GPI anchor. Initially, the conversion from PrP C to PrP Sc was thought to occur only when PrP C was bound to the cell membrane by the GPI anchor, but a study by Chesebro and coworkers showed the opposite.…”
Section: Prps That Lack the Gpi Anchor Anchorless Prpmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors characterized two patients with prion disease who carried stop mutations at positions Y226X and Q227X and expressed the respective forms. Using a monoclonal antibody V5B2 [89] that specifically binds to a fragment of PrP ending with Tyr226, we concurrently described the existence of a free form of PrP named PrP226* [90][91][92][93][94]. The distribution of PrP226* in the human brain has been associated with the distribution of PrP Sc [90,94].…”
Section: Shedding Of Prion Proteinmentioning
confidence: 99%